Estimation of average level of ordinary syzygy low tides in Paracas Bay - Jiménez, C. (2011)
The Earth is a dynamic system and as such is susceptible to the action of seismic and geological events. For many problems in science and engineering there is a need to establish a three-dimensional coordinate system for geodesic measurements. With the advancement of satellite geodesy, is currently possible to determine the horizontal coordinates of a point on the Earth’s surface with errors less than one centimeter. The problem arises when trying to obtain the vertical coordinate, since satellites provide heights with reference to an ellipsoid, which is not an equipotential surface. For obtaining the vertical coordinate, the reference surface of the geoid or mean level sea is taken. In the present study, a methodology to determine the mean sea level in the Paracas Bay is provided, using an ultrasonic level sensor interfaced to a computer. The data are digitally processed using filtering tools and Fourier transform to separate the frequency components corresponding to the tide and surge. The result is a reference level with an error of ±2 cm, which is sufficient for many engineering works.